Cryptocurrencies (IntechOpen, 2025)
Money is undoubtedly the fundamental element of the economy, and its history reflects the evolution of financial markets. Currently, we are witnessing significant technological advancements in payment methods, highlighting the potential benefits of introducing new means of economic exchange. Cryptocurrencies may emerge as a prominent form of payment in the future. Cryptocurrencies are an innovative and technologically advanced alternative to a fully globalized future. They represent a potential solution for processing payments across geographical borders. Additionally, if cryptocurrencies are effectively regulated through current adjustments, they will be able to help future generations navigate the complexities of financial transactions. Cryptocurrencies perform the same functions as traditional money, possessing attributes such as durability, divisibility, and originality. With social acceptance, they could become a legitimate means of exchange. Over the last decade or so, cryptocurrencies have gained popularity, and their importance in financial markets continues to grow. Their innovative nature has the potential to drive substantial changes and significantly impact the functioning of the global financial sector in the future. Cryptocurrencies – Financial Technologies of the Future provides knowledge, recommendations, and practical solutions to new challenges within the contemporary processes of globalization and international trade thanks to cryptocurrencies